Preoperative localization of the sensorimotor cortex and measurement of tumor perfusion in a single acquisition using ASL technique. (January 2019) - Kim, Ju Ho; Choi, Dae Seob; Park, Sung Eun; Choi, Ho Cheol; Koh, Eun Ha; Kim, Seong Hu
Highlights: Arterial spin labelling (ASL) is a noninvasive technique for measuring the cerebral blood flow. Resting state-fMRI with ASL can be used for the presurgical localization of the sensorimotor cortex. With ASL, all of brain perfusion, CBF measurement, and rs-fMRI can be obtained at a single acquisition. Abstract: Resting state fMRI (rs-fMRI) using arterial spin labelling (ASL) technique was performed for the preoperative localization of the sensorimotor cortex in a patient with lymphoma and the results were compared to those of task-based (tb) and rs-fMRI studies using blood oxygenation level-dependent (BOLD) sequence. Rs-fMRI using ASL showed similar results in the regions of the sensorimotor network to those of tb- and rs-fMRI fMRI using BOLD. ASL technique has a potential in clinical practice because all of brain perfusion imaging, cerebral blood flow measurement, and rs-fMRI study can be performed at a single acquisition.